Anak - Santos, Vilma; Barretto, Claudine; Torre, Joel.; Quintos, Rory B.; Lee, Ricardo E.; Star Cinema Productions Inc.; Regal Home Video (Quezon City Regal Home Video, 1999)
A domestic helper returns to the Philippines, where her 3 grown children reveal their resentment towards her. She's confused, as she had sacrificed to send money home. Her children, however, believe she had abandoned them. Life for everyone takes negative turns, and the mother is faced with a difficult choice: reclaim her family, or take the easy path and return to her old job.
Original production: c2000.
Also available in DVD.
Music, Jessie Lasaten ; editor, Geoge Jarlego ; cinematography, Joe Batac ; story and screenplay, Ricardo Lee, Raymond Lee ; produced by Trina N. Dayrit ; executive producers, Malou N. Santos, Charo Santos-Concio.
Vilma Santos, Claudine Barretto, Joel Torre ... [et al.].
VHS.
Donated by Prof. Amor Olaguer-Aljibe.
Keywords: Domestics -- Drama; Mother and child -- Drama; Feature films -- Philippines